2022
DOI: 10.37899/journallamultiapp.v3i5.710
|View full text |Cite
|
Sign up to set email alerts
|

A Osseointegration in Rabbit Model Using PEEK Coated by HA: Comparative Study for Histological and X-ray

Abstract: Biocompatible implants are often proposed to improve osseointegration such as metal, polymer, and ceramic to increase bone growth. This study aimed to create a new interface to enhance osseointegration. This interface is between the polymeric part and bone tissue. In this work coat PEEK (polyether ether ketone) plastic material coated with an active biocompatible material (hydroxyapatite). Regarding biocompatibility, coated PEEK was implanted inside the specimen in rabbit bone, the specimens were X-rayed after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
0
0
Order By: Relevance
“…This study indicated that the PEEK can be coated with HA by adjusting the appropriate values for CHI and the appropriate temperature by a dip coating method. Based on previously published research this way gives success in practice in the rabbits for the increased osseointegration [31].…”
Section: Resultsmentioning
confidence: 99%
“…This study indicated that the PEEK can be coated with HA by adjusting the appropriate values for CHI and the appropriate temperature by a dip coating method. Based on previously published research this way gives success in practice in the rabbits for the increased osseointegration [31].…”
Section: Resultsmentioning
confidence: 99%